200k views
4 votes
(3y - 3) + x

X=3
Y= 5

User Rafak
by
5.4k points

2 Answers

6 votes
The answer is 15. It’s important to remember PEMDAS like always, remember that. So you’re going to just plug in your Y and your X, so you’ll have (3x5 - 3) + 3
Remembering to do multiplication in the parentheses first, you’ll get (15-3) + 3. Then you finish the parenthesis and get 12+3, and then you finish the problem getting 15.
User Owenmelbz
by
5.5k points
6 votes

Plug in 5 for y, and 3 for x

(3(5) - 3) + (3)

First, multiply

5 x 3 = 15

Next, subtract

15 - 3 = 12

Finally, add

12 + 3 = 15

15 is your answer

hope this helps

User Jzeferino
by
5.3k points